Al-Maqsad al-Asna Sebagai Sebuah Karya Akidah al-Ghazali - Shuhari, Mohd Hasrul; Hamat, Mohd Fauzi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2014)
This article is a discourse on al-Maqsad al-Asna fi Sharh Asma’ Allah al-Husna, an intellectual book on the ‘Aqeedah (Islamic creed). The book was written by one of the most highly respected and recognized scholar in the Islamic world, Abu Hamid Muhammad ibn Muhammad al-Ghazali (d. 505H). This article is based on qualitative method which is content analysis on this book by al-Ghazali. The article will dwell on the a short background of al-Ghazali as the writer, the theme of the book, its contents and its references. This article will also look at unique characteristics of the book including its method of writing, its suitability to the target reader, its influence to religious scholars and the rationale of adopting it as a reference in the field of ‘Aqeedah. This article concludes that the book al-Maqsad al-Asna is one important academic work on ‘Aqeedah that should be referred to by the Muslims.